2021
DOI: 10.1016/s2352-3018(21)00151-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for COVID-19-related in-hospital mortality in a high HIV and tuberculosis prevalence setting in South Africa: a cohort study

Abstract: Background The interaction between COVID-19, non-communicable diseases, and chronic infectious diseases such as HIV and tuberculosis is unclear, particularly in low-income and middle-income countries in Africa. South Africa has a national HIV prevalence of 19% among people aged 15-49 years and a tuberculosis prevalence of 0•7% in people of all ages. Using a nationally representative hospital surveillance system in South Africa, we aimed to investigate the factors associated with in-hospital mortality among pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
152
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(168 citation statements)
references
References 32 publications
13
152
1
2
Order By: Relevance
“…We observed that in our cohort, COVID-19 disease severity was higher in PLWH, consistent with some of the larger epidemiological studies ( Western Cape Department of Health in collaboration with the National Institute for Communicable Diseases, South Africa et al, 2021 ; Geretti et al, 2021 ; Bhaskaran et al, 2021 ; Tesoriero et al, 2021 ; Braunstein et al, 2021 ; Jassat et al, 2021a ), although in this study differences were detected in the frequency of participants requiring supplemental oxygen and not in mortality. Our cohort may not be a typical ’hospitalized cohort’ as the majority of participants did not require supplemental oxygen.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that in our cohort, COVID-19 disease severity was higher in PLWH, consistent with some of the larger epidemiological studies ( Western Cape Department of Health in collaboration with the National Institute for Communicable Diseases, South Africa et al, 2021 ; Geretti et al, 2021 ; Bhaskaran et al, 2021 ; Tesoriero et al, 2021 ; Braunstein et al, 2021 ; Jassat et al, 2021a ), although in this study differences were detected in the frequency of participants requiring supplemental oxygen and not in mortality. Our cohort may not be a typical ’hospitalized cohort’ as the majority of participants did not require supplemental oxygen.…”
Section: Discussionsupporting
confidence: 92%
“…PLWH on supplemental oxygen also had lower frequencies of hypertension and diabetes. Age, hypertension, and diabetes are risk factors for more severe COVID-19 disease ( Yang et al, 2020 ; Guan et al, 2020 ; Ambrosioni et al, 2021 ; Jassat et al, 2021a ), and their absence may indicate that the more severe outcome is driven by another factor, with HIV infection being the simplest explanation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These key informant perspectives on the missed opportunity to strive for greater equity between the private and public health sectors were supported by the document analysis [ 41 , 49 ]. Although the private health sector provides care to less than 20% of the South African population, it accounted for the majority of COVID-19 tests during the first wave of infections [ 49 ].…”
Section: Resultsmentioning
confidence: 98%
“…Although the private health sector provides care to less than 20% of the South African population, it accounted for the majority of COVID-19 tests during the first wave of infections [ 49 ]. Evidence suggests that there is a lower threshold for admission to private hospitals, thus exacerbating inequities in access to COVID-19 treatment and care [ 41 ].…”
Section: Resultsmentioning
confidence: 99%